إجراءات اختيار السجلات الزلزالية وفقاً لمتطلبات بعض الكودات العالمية مقارنةً بالكود السوري - بسام حويجة; غسان شيخ علي; سراج جديد جديد (Tishreen University, 2016)
تعتمد بعض الكودات العالمية ومنها الأوربي، النيوزلندي، الأمريكي، الإيراني والسوري في عملية اختيار سجلات الحركات الأرضية من أجل التحليل بالسجل الزمني معياراً يتمحور حول التشابه بين الطابع السيسمولوجي للزلازل المستخدمة في التحليل وبين تلك المتوقعة الحدوث في الموقع المدروس، ولكنها تتبع منهجيات مختلفة. يشترط الكود النيوزلندي أن يطابق طيف الاستجابة لكل سجل مختار طيف الاستجابة التصميمي ضمن مجال محدد من الأدوار مرتبط بالدور الأساسي للمنشأ قيد التحقيق، ويجب أن تزيد الطاقة لطيف أحد هذه السجلات على الأقل طاقة طيف الاستجابة التصميمي. بينما يشترط الكود الأوربي أن يزيد الطيف المتوسط لجميع السجلات المختارة عن 90% من طيف التصميم في مجال الدور المحدد بشكل دائم، كما يجب أن تكون قيمة طيف الاستجابة المتوسط عند قيمة الدور المساوية للصفر أكبر من القيمة الموافقة لها على طيف الاستجابة التصميمي. وينصح الكود الأمريكي، كذلك الإيراني والسوري؛ أن يكون الطيف المتوسط للسجلات المختارة أكبر بـ 40% من طيف التصميم ضمن مجال محدد للدور. تعمل هذه الدراسة على إيضاح الاختلافات في إجراءات الاختيار وكيفية تأثير هذه الاختلافات في سجلات الحركات الأرضية القوية الناتجة، وتعرض بعض التوصيات الخاصة بإجراءات اختيار السجلات والتي ننصح باستخدامها بالإضافة إلى متطلبات الكود السوري. The European Standard, the New Zealand Standard, the U.S. Standard, the Syrian Standard and the Iranian Standard define a criterion for selecting ground motion records for time-history analysis by similarity between the seismological signature of earthquakes used for the analysis and those earthquakes that are expected to happen at the given location. But these standards follow different methodologies. The New Zealand Standard proposes that the spectrum of each selected record should match the design spectrum over a range of periods related to the fundamental period of the structure investigated. The energy of at least one of these record's spectra must exceed the energy of the design spectrum. The European Standard recommends that the average spectrum of the selected records should be always higher than 90% of the design spectrum in a defined range of periods, and the value of the average spectrum at period equal zero should be larger than the value of the corresponding design spectrum. The U.S. Standard, also the Syrian and the Iranian Standard; advise that in a defined range of periods, the average spectrum of the selected records should be 40% and higher than the code spectrum. This study illustrates the differences between selecting approaches, and how these differences affect the resulting ground motion records. Some resulting recommendations for record selecting procedures are presented, and advised to be used in addition to the Syrian Standard recommendations.